EFFECTS OF TEMPERATURE ON THE PHOTOSYNTHESIS OF THE ANTARCTIC GREEN ALGA, CHLORELLA VULGARIS (ABSTRACT) (15th Symposium on Polar Biology) - ナガシマ, ヒデユキ; ハヤシ, ナオリ; オオタニ, シュウジ; モモセ, ハルオ; NAGASHIMA, Hideyuki; HAYASHI, Naori; OHTANI, Shuji; MOMOSE, Haruo (National Institute of Polar Research, 1994)
P(論文) departmental bulletin paper